KAJIAN MANAJEMEN KONSTRUKSI PRODI TEKNIK SIPIL UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Mrs. Juanita (Universitas Muhammadiyah Purwokerto, 2011)
This study aims to analyze the views of professionals on the topics of materials in curriculum construction management and its application to construction projects. So the results can be used for curriculum development of construction management in civil engineering department UMP. Based on survey results obtained that the construction management topics are most important and frequently applied is the topic: 1) Consultants and Public Works are employment planning, job scheduling, work methods, and project supervision. 2) The contractor is planning work, scheduling, working methods and project costs. The topics are not important and not often applied to the contractor that is legal and licensing projects, and contract documents. Key words: construction management